Harmonization of Regulatory Authority between the Indonesian National Police and the National Narcotics Agency in the Use of Undercover Buy Techniques in Narcotics Crime Investigations - Arie Ramadhani; Roudhotul Jannah; Vava Ardila Raharjo (SINGOSARI, 2026)
The illicit trafficking of narcotics constitutes an organized transnational crime that requires special investigative techniques to uncover criminal networks. One such technique is the undercover buy or controlled purchase. The problem arises because the regulation of authority concerning the use of this technique creates disharmony between the Indonesian National Police (POLRI) and the National Narcotics Agency (BNN). Law Number 35 of 2009 on Narcotics explicitly grants this authority to BNN investigators, while the authority of POLRI investigators relies more heavily on internal police regulations. This condition leads to legal uncertainty, divergent interpretations, and potential jurisdictional overlaps in investigative practice. This study aims to analyze the form of regulatory disharmony between POLRI and BNN authorities in using the undercover buy technique and to formulate a harmonization model that can strengthen legal certainty and the effectiveness of narcotics law enforcement. The research employs a normative legal method with statutory, conceptual, case, and comparative approaches. The analysis examines legislation, court decisions, legal doctrines, and relevant scientific literature. The results indicate that disharmony occurs both vertically and horizontally. Vertically, inconsistencies exist between the Narcotics Law, the Criminal Procedure Code, and the Police Law. Horizontally, the unclear relationship of authority between POLRI and BNN creates a dualism in the implementation of the undercover buy technique. Regulatory harmonization is required through norm alignment, clear delineation of authority, and the establishment of inter-agency coordination mechanisms to ensure that the implementation of special investigative techniques continues to guarantee legal certainty, justice, and the protection of human rights.